OVERVIEW OF COMPLIANCE WITH THE HEALTH PROTOCOL IN TRADITIONAL MARKET TRADERS AND MODERN MARKETS - Tria Astika Endah Permatasari; Novita Ridha Amelia; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
The Covid-19 infection impacts the high risk of death of the sufferer. The market is the most vulnerable place for the risk of Covid-19 transmission because it is a gathering place that has the potential to become a cluster for the spread of Covid-19. Bogor Regency was ranked fourth in West Java Province, with 203 confirmed cases of Covid-19 and 15 deaths (7.38%). This study aimed to see an overview of market traders' compliance with health protocols to prevent the spread of Covid-19 in traditional and modern markets in Babakan Madang District, Bogor Regency. The research method was carried out using a cross-sectional design of 240 traders (120 traders in traditional markets and 120 traders in modern markets) in Babakan Madang District, Bogor Regency) which were calculated based on the hypothesis 2 test formula of population proportions and selected using a systematic random technique sampling. Data collection was carried out primarily with a structured questionnaire instrument. The dependent variable is the compliance of market traders, and the independent variables include sociodemographic factors, knowledge, the role of market managers, and traders' perceptions of the vulnerability of Covid-19 transmission. The time of data collection was from March-June 2022. Data analysis was carried out univariately. Most traditional and modern market traders comply with the Covid-19 Health protocol by 53.3%, while market traders who do not comply are 46.7%. The health protocol most market traders comply with is spraying disinfectant on stalls/kiosks by 68.3%.